ABSOLUTE CONFIGURATION OF 13-EPIMULINOLIC ACID - Brito, Iván; Borquez, Jorge; Cárdenas, Alejandro; Avendaño, Maria; Simirgiotis, Mario (Journal of the Chilean Chemical Society, 2017)
The molecular structure of the title compound [iupac name: 13-epi-8–hydroxy-3-isopropyl-5a,8-dimethyl-2,3,4,5,5a,6,7,8,10a,10b-decahydrocyclohepta[e] indene-3a(1H) acid] is similar to the structure of the known compound mulinolic acid.The structure of this mulinolic acid epimer consists of a mulinane skeleton and the isopropyl, methyl group, carboxylic acid and the hydroxyl group at C3, C8, C5, C13, respectively, which are β-oriented, whereas the methyl group at C13 are α-oriented. The cyclopentane (A), ciclohexane (B) and cicloheptene (C) rings are trans (A/B) and (B/C) cis fused, and are in an envelope, chair, and twist chair conformation respectively. In the crystal the molecules are linked by two strong intermolecular OH⋅⋅⋅O hydrogen bond forming bidimensional supramolecular structures with graph-set notation (12) and (46).The absolute configuration of the title compound which has been determined from the refinement of the Flack parameter16. On this basis the absolute configuration was assigned as C3R, C5S, C8S, C9S, C10S and C13S.